Single phase inverter for commercial use / Hatta Ariffin - Ariffin, Hatta (1996)
This report describes the development of a single phase inverter for commercial use. The work investigates how an inverter circuit can be developed in order to produce an ac supply with ratings of 240 Vac, 6 A and 50 Hz from an ordinary existing car battery of 12 Vdc. The proposed system consists of four modular circuits; oscillator which is formed using Wein-Bridge circuit and ac amplifier, preamplifier, push-pull power amplifier, and feedback circuit. In this work, WeinBridge oscillator is chosen to generate stable periodic signal and it is coupled with an amplifier to boost up the signal. Applications of this work includes portable ac power supply.